Treatments for Female Victims of Intimate Partner Violence: Systematic Review and Meta-Analysis - Karakurt, Günnur; Koç, Esin; Katta, Pranaya; Jones, Nicole; Bolen, Shari D. (Frontiers in Psychology, 2022)
Intimate partner violence (IPV) is an important problem that has significant detrimental effects on the wellbeing of female victims. The chronic physical and psychological effects of intimate partner violence (IPV) are complex, long-lasting, chronic, and require treatments focusing on improving mental health issues, safety, and support. Various psycho-social intervention programs are being implemented to improve survivor wellbeing. However, little is known about the effectiveness of different treatments on IPV survivors' wellbeing. For this purpose, we conducted a systematic review and meta-analysis to assess the effectiveness of interventions on improving outcomes that describe the wellbeing of adult female survivors of IPV. We searched PubMed, PsycINFO, and Cochrane Library. We explored the effectiveness of available interventions on multiple outcomes that are critical for the wellbeing of adult female victims of IPV. To provide a broad and comprehensive view of survivors' wellbeing, we considered outcomes including mental health, physical health, diminishing further violence, social support, safety, self-efficacy, and quality of life. We reviewed 2,770 citations. Among these 25 randomized-controlled-study with a total of 4,683 participants met inclusion criteria. Findings of meta-analyses on interventions indicated promising results in improving anxiety [standardized mean difference (SMD) −7.15, 95% confidence interval (CI) −8.39 to −5.92], depression (SMD −0.26, CI −0.56 to −0.05), safety (SMD = 0.43, CI 0.4 to −0.83), violence prevention (SMD = −0.92, CI −1.66 to −0.17), health (SMD = 0.39, CI 0.12 to 0.66), self-esteem (SMD = 1.33, CI −0.73 to 3.39), social support (SMD =0.40, CI 0.20 to 0.61), and stress management (SMD = −8.94, CI −10.48 to −7.40) at the post-test. We found that empowerment plays a vital role, especially when treating depression and Post-Traumatic Stress Disorder (PTSD), which are difficult to improve across interventions. We found mixed findings on self-efficacy and quality of life. The effects of IPV are long-lasting and require treatments targeting co-morbid issues including improving safety and mental health issues.